Effect of various zinc concentrations on some morphological parameters at tomato (Lycopersicon esculentum Mill.) - Cvetanovska, Lenka; Spasenoski, Mirko (Macedonian Journal of Ecology and Environment, 2001)
The investigations have been carried out with tomato plants cv.Saint Pierre grown in hydroponics on modified Hogland’s nutrient solution with different Zn concentrations. In the course of these investigations has been established that the optimal Zn concentrations of treatment which had a favorable effect on the biometric indices, on macro and microelement content, varied within a range od 0,67-3,34 mM. Concentrations of 13,40 as well as 1339,42 mM zinc were toxic and inchibited greatly growth, sugar and chloroplast pigments production in aboveground parts.